2012
DOI: 10.1089/thy.2010.0154
|View full text |Cite
|
Sign up to set email alerts
|

Metastases to the Thyroid: A Review of the Literature from the Last Decade

Abstract: It is important to keep in mind that the thyroid gland can be a site of metastases for a variety of tumors when evaluating a thyroid nodule, especially in a patient with a prior history of malignancy. In patients with thyroid lesions and a history of malignant disease, regardless of time elapsed since the initial diagnosis of the primary neoplasm, disease recurrence or progression of malignancy must be considered until proven otherwise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
391
4
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(425 citation statements)
references
References 112 publications
16
391
4
14
Order By: Relevance
“…Studies have suggested that metastatic disease to thyroid may be more common in diseased thyroid such as thyroiditis or goiter [11]. One recent literature review suggests that 44.2% of metastasis occurred in diseased thyroid gland [3]. It is important to highlight here that our patient also has a history of long standing goiter which developed metastatic disease later in the course.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Studies have suggested that metastatic disease to thyroid may be more common in diseased thyroid such as thyroiditis or goiter [11]. One recent literature review suggests that 44.2% of metastasis occurred in diseased thyroid gland [3]. It is important to highlight here that our patient also has a history of long standing goiter which developed metastatic disease later in the course.…”
Section: Discussionmentioning
confidence: 81%
“…However, initial diagnostic test of choice is FNAC. Chung et al reviewed patients of metastatic disease to thyroid from non-thyroid malignancies and reported that FNAC provided exact diagnosis in 73.7% of the patients [3]. If inconclusive, biopsy and immunohistochemistry should be performed [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Combined diagnoses are common in the thyroid and are frequently represented by the mixture of cell populations aspirated. The hyperplastic, inflammatory, or even neoplastic background makes the identification of metastasis more difficult [30,31,34]. …”
Section: Discussionmentioning
confidence: 99%